Comprehensive flood risk management : research for policy and practice : proceedings of the 2nd European Conference on Flood risk management, Floodrisk 2012, Rotterdam, the Nederlands, 19-23 november 2012 - Klijn, Frans; Schweckendiek, Timo; Klijn, Frans; Schweckendiek, Timo (CRC Press, 2013)
Flood risk management policy across the European Union is changing, partly in response to the EU Floods Directive and partly because of new scientific approaches and research findings. It involves a move towards comprehensive flood risk management, which requires bringing the following fields/domains closer together: the natural sciences, social sciences and arts; science, policy and practice; and engineering, spatial planning and governance. Naturally, this involves preventive fl ood risk management and flood event management, as well as learning from the past and considering future global ch.